Accessibility Planning for Postsecondary Entrance and Placement Exams for Deaf Students. (May 2022) - Cawthon, Stephanie W.; Goldstone, Linda; Higgins, Jennifer; Thurlow, Martha
Postsecondary entrance and placement tests provide critical information that shapes the trajectory of the transition from secondary to postsecondary education. Test accommodations can play an important role in reducing barriers that deaf students face during high-stakes testing. For deaf students, decisions about access and accommodations for standardized assessment typically involve an Individualized Education Program (IEP) team. Deaf students' access needs are not homogeneous, and decisions include a variety of factors including student characteristics, the content of the test, and test accommodations policies. In this article we share information about challenges that deaf students face and suggestions for ways to help to ensure that deaf students receive the accommodations that better allow them to show what they know and can do. These steps to improve accessibility can support equity in postsecondary pathways for deaf students.